The Influence of Self Talk on Badminton Athletes Anxiety Before Competitions - Sitawaty Tjiptorini; Anggi Esa Oktaviani (International Journal Labs, 2022)
To become outstanding badminton athletes one must have a champion mentality especially when facing competitions. However, it is not uncommon for an athlete, even though he/she has learned many techniques to play badminton for a long time, anxiety still arises before any match. The factors behind athlete anxiety before the match may come from within the athlete, especially the athlete's personal conversations or self talk. This research aim to understand the influence of self talk on athlete anxiety before competitions. Quantitative method is used on 107 badminton athletes from various badminton clubs in Indonesia by filling out questionaires online using incidental sampling technique. The population of this research were male and female badminton athletes, between the age of 18–27 years old, from various badminton clubs throughout Indonesia who participated in, had been, or were in a competition. The Sport Anxiety Scale-2 (SAS-2) from Smith et al. (2006) and updated by Rice, et al (2019) was used to measure competition anxiety. Also, The Automatic Self-Talk Questionnaire (ASTQ) from Zourbanos, et al, (2009) and updated by Latinjak & Zourbanos, N. (2017) was used to measure self talk. The results of the study obtained the value of r = 0.631 and R sq = .393 (p < 0.05). The result indicate that there is a significant positive influence of self talk on athletes anxiety before competitions. Therefore, the more self talks of the badminton athletes before the match, the higher the athlete anxiety. However, the result also show that mostly negative self talks in the dimensions of the scale contribute greatly to the athlete anxiety.